2018
DOI: 10.31557/apjcp.2018.19.11.3279
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 Prognostic Value in Different Histological Grades of Oral Epithelial Dysplasia and Oral Squamous Cell Carcinoma

Abstract: Introduction:Abnormal cell proliferation appears to be a possible predictor of tumorigenesis, Ki-67 protein expression is closely related to the cell proliferation and could be used as a biomarker for the growth in the most of human tumors. The aim of the study: Investigating of Ki-67 expression in the pathological grades of oral epithelial dysplasia and oral squamous cell carcinomas.Materials and Methods:The sample consisted of 30 formalin-fixed, paraffin-embedded specimens of oral epithelial dysplasia (OED),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 62 publications
10
41
0
3
Order By: Relevance
“…Ki-67 is a nuclear protein present during all active phases of the cell cycle (G1, S, G2, and M), but is absent in resting cells (G0) [31]. Ki67 + cells are mainly located along the basal layer of nasal epithelium and specifically located in basal cells, indicating that cell proliferation in nasal epithelium mainly occurred in basal cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 is a nuclear protein present during all active phases of the cell cycle (G1, S, G2, and M), but is absent in resting cells (G0) [31]. Ki67 + cells are mainly located along the basal layer of nasal epithelium and specifically located in basal cells, indicating that cell proliferation in nasal epithelium mainly occurred in basal cells [16].…”
Section: Discussionmentioning
confidence: 99%
“…No statistical noteworthy distinction was present amid NOE and mild OED, this shows that the pace of carcinomatous change is more in entities that display moderate to severe dysplasia. [ 11 ] There was a statistical noteworthy distinction in the expression of Ki-67 among well-differentiated OSCC, moderately differentiated OSCC, poorly differentiated OSCC, and NOM, this shows that the appearance of Ki‑67 amplified progressively with the increase of differentiation of OSCC. Macluskey et al [ 12 ] showed statistical noteworthy relation with mean Ki‑67 in healthy tissue, dysplasia, and in carcinomatous tissue, thus suggestive of increase in epithelial propagation throughout the changeover from dysplasia to cancer [ Table 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…We saw that the cell proliferation in OSCC expanded with increasing histological grades of OSCC. Comparable outcomes were accounted by Takkem et al [ 11 ] and Tumuluri et al [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 is a nuclear protein present during all active phases of the cell cycle (G1, S, G2, and M), but is absent in resting cells (G0) [29]. Ki67 + cells are mainly located along the basal layer of nasal epithelium and speci cally located in basal cells, indicating that cell proliferation in nasal epithelium mainly occurred in basal cells [16].…”
Section: Discussionmentioning
confidence: 99%